SPOT SPEED LIMIT STUDIES OF AGAIE-KATCHA-BARO ROAD AGAIE, NIGER STATE - Wada, Surajo Abubakar; Labbo, Muwaffaq Safiyan; Kenchi, Abdulkadir Yunusa (FUDMA JOURNAL OF SCIENCES, 2021)
The number of accidents in Nigeria increases relatively from year to year, despite the fact that there are many programs organized by the authority to reduce them. Several factors contribute to the occurrence of accidents. Some of which are human behavior, vehicles condition, weather conditions, road surfaces, and road alignments (vertical and horizontal curves). This research presents empirical research to estimate the 85th percentile operating speed limits. The speed data were obtained using a stopwatch on the selected location along the Agaie-Katcha-Baro Road Agaie, Niger State. Spot speed study was adopted as the method for the research. The method has successfully predicted the 85th percentile speed limit for the Agaie-Katcha-Baro Road Agaie, Niger State. It has established maximum and minimum speed limits for the road and has also shown how inexpensive and quick the stopwatch method is in conducting spot speed studies in Nigerian roads. The findings are hoped to provide a lasting solution towards the national design standard for the highway designer and planner to improving the consistency of geometric design elements of the two-lane highways.
Keywords: Spot speed limit, Accident, 85th percentile operating speed limit, road surface conditions